2007
DOI: 10.1111/j.1440-1827.2007.02083.x
|View full text |Cite
|
Sign up to set email alerts
|

Advanced malignant solitary fibrous tumor in pelvis responding to radiation therapy

Abstract: Solitary fibrous tumor (SFT) is a rare spindle cell neoplasm that is benign in most cases. Although SFT was first recognized to arise only in the pleura, recent reports indicate that SFT can involve a wide range of anatomical sites. To date, 17 cases of pelvic SFT have been reported. Herein is reported a case of a 74-year-old woman with a giant malignant SFT in the pelvis. Along with massive invasion to adjacent organs and multiple lung metastases detected on radiography, biopsy from the tumor through the vagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 19 publications
1
37
0
2
Order By: Relevance
“…Formerly, Kawamura et al reported a patient with SFT, localized in pelvis, who had multiple lung metastases, who had significant response to pelvic radiotherapy with total 50 Gy dose [9]. On the contrary, Dietrich et al indicated accelerated progression at the lesion in the course of Axial CT scan of the chest showing shrinkage at the lesion 6 weeks later from 60 Gy/30fx RT radiotherapy in a patient with SFT, which localized at the thoracic wall [10].…”
Section: Discussionmentioning
confidence: 96%
“…Formerly, Kawamura et al reported a patient with SFT, localized in pelvis, who had multiple lung metastases, who had significant response to pelvic radiotherapy with total 50 Gy dose [9]. On the contrary, Dietrich et al indicated accelerated progression at the lesion in the course of Axial CT scan of the chest showing shrinkage at the lesion 6 weeks later from 60 Gy/30fx RT radiotherapy in a patient with SFT, which localized at the thoracic wall [10].…”
Section: Discussionmentioning
confidence: 96%
“…Based on the pathological features and the clinical presentation, the diagnosis of hypervascular malignant SFT was made. Then, based on a few previous reports [5,6], we planned preoperative radiation therapy in an attempt to reduce the risk of bleeding during the operation. Adequate information concerning the risks and benefits of the different kinds of therapeutic modalities was given, and the patient chose the performance of preoperative radiation therapy.…”
Section: Case Reportmentioning
confidence: 99%
“…Studies of pleural SFT were prolific in the 1980s, and the largest study indicated that SFT occurred almost equally in both sexes (195 female, 165 male) and that it occurred in all age groups (range 5-87 years, average 51 years) [5,8]. The reported tumor size ranged from 1-33 cm (average 11 cm), and the malignant potential was reported to be 12 % [5]. On the other hand, various extrapleural SFTs have been reported since the 1990s.…”
Section: Case Reportmentioning
confidence: 99%
See 2 more Smart Citations